Analisis Filosofis terhadap Kriminalisasi Pernikahan Kedua pada Pasal 402 KUHP No. 1 Tahun 2023 - Siti Kholizah; Seva Maya Sari (Sanskara Hukum dan HAM, 2026)
This research is aimed at examining the philosophical foundation underlying the criminalization of second marriages as regulated under Article 402 of Law Number 1 of 2023 concerning the Indonesian Penal Code, while also analyzing the issue from the standpoint of Islamic criminal law. The study adopts a normative juridical method, drawing on statutory, conceptual, and comparative approaches. Legal materials were gathered through library-based research, encompassing legislation, legal literature, and pertinent academic journals, which were subsequently examined using qualitative analysis. The findings indicate that the criminalization under Article 402 is founded on the principles of open monogami, legal certainty, justice, and the protection of the rights of women and children. Criminal sanctions are regarded as the application of the ultimum remedium principle to preserve the legal order of marriage rather than as an absolute prohibition of polygamy. From the perspective of Islamic criminal law, this provision is consistent with Islamic principles because polygamy remains permissible provided that the requirements of justice and applicable legal procedures are fulfilled. The sanction for violating these requirements may be classified as ta'zir, aiming to achieve public welfare, particularly the protection of lineage (hifz al-nasl). Therefore, Article 402 reflects philosophical values that are consistent with the objectives of Indonesia's criminal law reform and the principles of Islamic criminal law.